PENGARUH METODE GAMES BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI FIKIH KELAS V DI MI TARBIYATUL ATHFAL - Aziziyah, Ulfi; Supriatna, Asep; Syach, Alfyan (Penerbit Lafadz Jaya, 2025)
This study was conducted to examine the influence of the Game-Based Learning (GBL) method on the learning outcomes of fifth-grade students in the fiqh ibadah subject at MI Tarbiyatul Athfal. The research problem stemmed from the fact that students’ academic performance remained below expectations, as indicated by an average Mid-Semester Examination score of 62.75, which did not meet the Minimum Mastery Criteria of 70. This condition was further reinforced by the teacher’s reliance on monotonous instructional strategies, which limited students’ motivation and achievement. A quantitative approach with a quasi-experimental design (Nonequivalent Control Group Design) was employed. The participants consisted of 27 students, divided into 12 students in the experimental group who were taught using GBL, and 15 students in the control group who continued learning through the lecture method. Data were gathered through pretests and posttests, classroom observations, and supporting documentation. The analysis was descriptive, focusing on comparing the results before and after the treatment. The findings revealed a considerable improvement in the experimental group, where the mean score rose from 62.75 in the pretest to 73.75 in the posttest. In addition, the distribution of achievement categories shifted positively, with the elimination of the very low category and an increase in the proportion of students in the high category. Although the control group also showed progress, the gains were less significant compared to the experimental group. In conclusion, the GBL method proved effective in improving students’ comprehension of fiqh ibadah while creating a more engaging and interactive learning environment. Thus, this approach is recommended as an innovative instructional alternative in primary education.